Absorption, Translocation, and Metabolism of Halosulfuron in Cucumber, Summer Squash, and Selected Weeds. Issue 4 (20th June 2017) - Besançon, Thierry. E.; Jennings, Katherine M.; Everman, Wesley J.
Abstract : Greenhouse studies were conducted to investigate the absorption, translocation, and metabolism of foliar-applied [ 14 C]halosulfuron-methyl in cucumber, summer squash, pitted morningglory, and velvetleaf. Cucumber and summer squash were treated at the 4-leaf stage, whereas velvetleaf and pitted morningglory were treated at 10 cm. All plants were collected at 4, 24, 48, and 72 h after treatment (HAT) for absorption and translocation studies and an additional 96-HAT interval was included in the metabolism study. Absorption did not exceed 45% in summer squash, whereas it plateaued around 60% in velvetleaf and cucumber and reached 80% in pitted morningglory 72 HAT. None of the four species translocated more than 23% of absorbed halosulfuron out of the treated leaf. Translocation in cucumber and summer squash was predominantly basipetal, while acropetal movement prevailed in velvetleaf. No significant direction of movement was observed for pitted morningglory. Negligible translocation occurred toward the roots, regardless of plant species. Of the total amount of [ 14 C]halosulfuron-methyl absorbed into the plants at 96 HAT, more than 80% remained in the form of the parent compound in velvetleaf, summer squash, and pitted morningglory, whereas less than 20% was detected in cucumber. Rapid and high herbicide metabolism may explain cucumber tolerance to halosulfuron-methyl, while lack of metabolism contributes to summer squash and velvetleaf susceptibility. Pitted morningglory tolerance may be due to limited translocation associated with some level of metabolism, but further research would be needed to investigate other potential causes.